Developing STEM competencies for pre-service mathematics teachers - Nguyen, Thi Thu Ha; Doan, Van Hai; Nguyen, Van Thanh Thi; Gam, Nguyen Thi Hong (Edelweiss Applied Science and Technology, 2026)
In the context of ongoing educational reform in Vietnam, STEM education has emerged as a significant direction in mathematics teacher preparation. This study investigates the current state and effectiveness of developing STEM competencies among pre-service mathematics teachers through an experimental–control pre-test–post-test design conducted at Hai Duong University (Hai Phong, Vietnam). The participants included over 200 undergraduate students majoring in Mathematics Education from cohorts K13, K14, and K15 who engaged in STEM-integrated course modules. Data were collected through questionnaires, classroom observations, analysis of learning products, and competency assessments. The findings indicate significant improvements in students’ STEM competencies after the intervention, particularly in real-world problem solving, the design of integrated instructional activities, and the application of technology in mathematics teaching (p < 0.05). Nevertheless, some students continued to face challenges in meaningfully integrating mathematical concepts with scientific and engineering contexts. The study provides empirical evidence supporting the implementation of STEM-oriented instructional models in mathematics teacher education and offers recommendations to enhance STEM competency development in university-level teacher preparation programs.